Public health and centenarians: necessary adjustments and an uncertain future - Wachholz,Patrick Alexander (2016)
In a global population aging scenario, achieving 100 years and older is no longer an isolated incident: in Brazil there are already more than 24 thousand centenarians, and in some countries this segment will increase about 700% till 2050, when approximately 3 million centenarians are estimated in the world. Despite being a social, economic and technological triumph, the growth of centenarians is associated with significant challenges to traditional models of security and social support, as well as a potential problem for public health policies. In this paper we propose to present our opinions about this theme, to revise the implications to public health of the exponential increase in the number of centenarians, highlighting the importance of developing a national research agenda in Brazil involving this issue. We also discussed propositions on the reorientation of public health policies models, focusing on this age group..